Burosumab for X-linked hypophosphatemia in children and adolescents: Opinion based on early experience in seven European countries - Mughal, M. Zulf; Baroncelli, Giampiero I.; de Lucas-Collantes, Carmen; Linglart, Agnès; Magnolato, Andrea; Raimann, Adalbert; Santos, Fernando; Schnabel, Dirk; Shaw, Nick; Nilsson, Ola (Frontiers in Endocrinology, 2023)
Given the relatively recent introduction of burosumab in the management of X-linked hypophosphataemia (XLH), there is a lack of real-world data to guide its use in clinical practice. As a group of European physicians experienced with burosumab treatment in clinical practice, we convened with the objective of sharing these practice-based insights on the use of burosumab in children and adolescents with XLH. We attended two virtual meetings, then discussed key questions via Within3, a virtual online platform. Points of discussion related to patient selection criteria, burosumab starting dose, dose titration and treatment monitoring. Our discussions revealed that criteria for selecting children with XLH varied across Europe from all children above 1 year to only children with overt rickets despite conventional treatment being eligible. We initiated burosumab dosing according to guidance in the Summary of Product Characteristics, an international consensus statement from 2019 and local country guidelines. Dose titration was primarily guided by serum phosphate levels, with some centres also using the ratio of tubular maximum reabsorption of phosphate to glomerular filtration rate (TmP/GFR). We monitored response to burosumab treatment clinically (growth, deformities, bone pain and physical functioning), radiologically (rickets and deformities) and biochemically (serum phosphate, alkaline phosphatase, 1,25-dihydroxyvitamin D, 25-hydroxyvitamin D, urine calcium-creatinine ratio and TmP/GFR). Key suggestions made by our group were initiation of burosumab treatment in children as early as possible, from the age of 1 year, particularly in those with profound rickets, and a need for clinical studies on continuation of burosumab throughout adolescence and into adulthood.